Cartilage Repair Strategies - Williams, Riley J. (Humana Press : Imprint: Humana, 2007)
Cartilage Repair Strategies is a comprehensive update of the present state of cartilage repair and regeneration. The information in this volume addresses what methods are effective, what methods are safe, and what methods will lead to an alteration in the short history of articular cartilage injury repair. Contributors present examinations of a variety of topics including the structure and function of articular cartilage, the evaluation of cartilage repair techniques, and the latest cartilage sensitive imaging techniques. Several chapters anticipate new and emerging cartilage repair techniques - such as second generation ACI, resorbable scaffold-based repair, and arthroscopically performed cartilage transplantation - and include descriptions of the rationale and application of these procedures. Leading experts present updates on current and emerging methodologies, making Cartilage Repair Strategies a unique and essential reference.